Strategies on enhancing marketability and employability of Quantity Surveing’s graduates from Faculty of Architecture, Planning and Surveying (FSPU), UiTM Cawangan Sarawak, Kampus Samarahan / Clerinty Indi - Indi, Clerinty (2019)
Fresh graduates’ rate of unemployment is high due to lack of skills for the job application. Part of the criteria of the job application are soft skills, technological skills and personal qualities and people skills. This research aimed to investigate how the faculties can create strategies to increase the employability and marketability of the graduates. The research focused on the graduates and lecturers of the Department of Quantity Surveying UiTM Kampus Samarahan, and employers in Sarawak construction industry. The study was done based on questionnaires and observation within the scope stated. The data were presented in tabulation of frequency and percentage methods. The research found that the graduates the strategies created by the faculty were able to increase the work readiness of the industry. Apart from that, it was found that there are six attributes that were important to be practiced by the graduates, consisting of team work skills, integrity skills, problem solving skills, ICT skills, critical thinking skills and decision making skills. As a conclusion, the department, and the graduates themselves have important role in ensuring that they are able to be employed in construction industry.